SNPs in inflammatory genes CCL11, CCL4 and MEFV in a fibromyalgia family study. - Zhifang Zhang; Jinong Feng; Allen Mao; Keith Le; Deirdre La Placa; Xiwei Wu; Jeffrey Longmate; Claudia Marek; R Paul St Amand; Susan L Neuhausen; John E Shively (PLoS ONE)
Background Fibromyalgia (FM) is a chronic pain syndrome with a high incidence in females that may involve activation of the immune system. We performed exome sequencing on chemokine genes in a region of chromosome 17 identified in a genome-wide family association study. Methods and findings Exome sequence analysis of 100 FM probands was performed at 17p13.3-q25 followed by functional analysis of SNPs found in the chemokine gene locus. Missense SNPs (413) in 17p13.3-q25 were observed in at least 10 probands. SNPs rs1129844 in CCL11 and rs1719152 in CCL4 were associated with elevated plasma chemokine levels in FM. In a transmission disequilibrium test (TDT), rs1129844 was unequally transmitted from parents to their affected children (p< 0.0074), while the CCL4 SNP was not. The amino acid change (Ala23Thr), resulting from rs1129844 in CCL11, predicted to alter processing of the signal peptide, led to reduced expression of CCL11. The variant protein from CCL4 rs1719152 exhibited protein aggregation and a potent down-regulation of its cognate receptor CCR5, a receptor associated with hypotensive effects. Treatment of skeletal muscle cells with CCL11 produced high levels of CCL4 suggesting CCL11 regulates CCL4 in muscle. The immune association of FM with SNPs in MEFV, a chromosome 16 gene associated with recurrent fevers, had a p< 0.008 TDT for a combined 220 trios. Conclusions SNPs with significant TDTs were found in 36% of the cohort for CCL11 and 12% for MEFV, along with a protein variant in CCL4 (41%) that affects CCR5 down-regulation, supporting an immune involvement for FM.